Work Based Learning Combined with E-Learning for Acquisition of Management Competences - Soeiro, Alfredo Vieira (International Journal of Advanced Corporate Learning (iJAC), 2013)
Partners in E-View project developed and piloted a European Virtual Campus aimed at learners in the work place which focused on enhancing their management skills and competences within a European context. The project began with a needs analysis followed by the creation of the Virtual Campus Framework. This framework utilized a customised open source delivery methodology and a work-based learning module based on the needs analysis aimed at training managers in European enterprises. The module with an emphasis on working within Europe was piloted with about one hundred employees in the UK, Poland, Portugal and Ireland involving four employers. Concrete outcomes from E-View included a Virtual Campus Framework for Work-based learning (WBL) with a sample undergraduate module, two rounds of pilot courses and an online handbook with a description of the experiences gained in creating and delivering this course in the Virtual Campus Framework for Work-based Learning. Webinars were delivered and recorded to illustrate the procedures.